Learning to unlearn faulty beliefs and practices in English language teaching - Willy Ardian Renandya; Minh Nguyen Thi Thuy; George Martin Jacobs (Universitas Syiah Kuala, 2023)
Our actions arise from our beliefs about life: what we need and how best to achieve it. This article asks English language teachers to undertake an open-minded examination of some long-held beliefs in our profession and of the teaching practices that derive from those beliefs. Perhaps, based on this examination, teachers may wish to modify some beliefs and, correspondingly, change some practices. The particular beliefs examined in the article are as follows: people who begin second language learning at a younger age will be more successful than those who start at an older age; native speaker varieties of English (e.g., those spoken native-English speaking countries) should be valued over non-native varieties (e.g., those spoken in outer and expanding circle countries); the best outcome is for second language learners to use English only and stop using their mother tongue in and out of the classroom; in second language instruction, systematic, explicit and detailed instruction of grammar deserves top priority; vocabulary is considered less important than grammar; pragmatic competence need not be taught as students can acquire it on their own; learning depends on suffering, thus the famous saying "no pain, no gain"; teaching learning strategies deserves a great deal of attention; teaching materials should be difficult in order to move learning forward, and only lazy and uninformed teachers use cooperative learning.